2014
DOI: 10.1038/onc.2014.401
|View full text |Cite
|
Sign up to set email alerts
|

The role of TXNDC5 in castration-resistant prostate cancer—involvement of androgen receptor signaling pathway

Abstract: Castration-resistant prostate cancer (CRPC) continues to be a major clinical problem and the mechanisms behind it remain unclear. Thioredoxin domain-containing protein 5 (TXNDC5) is involved in protein folding and chaperone activity, and its overexpression has been reported in multiple malignancies. In the current study, we demonstrated that TXNDC5 is up-regulated following long-term androgen-deprivation treatment (ADT) and is highly overexpressed in CRPC tumors compared with hormone-naive prostate cancer (PCa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 40 publications
5
56
0
Order By: Relevance
“…Knockdown of ERp46 demonstrated more significant results on tumor growth in vivo compared with overexpression, which may be due to an already robust expression level of ERp46 in the parental cells. Similar to the results of the present study, ERp46 overexpression also induced an increased tumor cell growth rate in human prostate adenocarcinoma LNCaP cells, in vitro and in vivo (8). This was revealed to be at least in part due to increased androgen receptor stability and signaling in the presence of increased ERp46 (8).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Knockdown of ERp46 demonstrated more significant results on tumor growth in vivo compared with overexpression, which may be due to an already robust expression level of ERp46 in the parental cells. Similar to the results of the present study, ERp46 overexpression also induced an increased tumor cell growth rate in human prostate adenocarcinoma LNCaP cells, in vitro and in vivo (8). This was revealed to be at least in part due to increased androgen receptor stability and signaling in the presence of increased ERp46 (8).…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the results of the present study, ERp46 overexpression also induced an increased tumor cell growth rate in human prostate adenocarcinoma LNCaP cells, in vitro and in vivo (8). This was revealed to be at least in part due to increased androgen receptor stability and signaling in the presence of increased ERp46 (8). Accordingly, in the in vivo experiments of the present study, a significant reduction of PSA secretion, a potential indication of tumor volume, was identified following knockdown of ERp46 (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This kind of imperfect complementarity with target ensures that miRNAs have multiple intracellular targets that lead to amplification of the biological effects [6,7]. Thus, the exact role of miR-200b in AIPC remains unclear although a subsequent study demonstrated that miR-200b mediates HIF1α-induced TXNDC5 expression under ADT conditions [8].…”
Section: Introductionmentioning
confidence: 99%